Assessment of Nephroprotective Potentials of Citrus aurantifolia (Christm) Swingle Peels Extract in Gentamicin-Induced Kidney Toxicity in Mice (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Peels from Citrus aurantifolia are used in ethnomedicine to cure a variety of illnesses. These extracts have been used traditionally as cold treatments, anti-inflammatory, and antibacterial agents, suggesting that they could be used in contemporary nephroprotective drugs.Objective: The objective of this investigation was to assess the nephroprotective properties of Citrus aurantifolia peels extract (CAPE) in gentamicin-induced kidney toxicity.Method: Dried Citrus aurantifolia peels were extracted with 80% methanol. Thirty mice were randomly assigned to six groups (Groups 1-6, n = 5). Group I received normal saline only (10 mL/kg; baseline), while Groups II, III, IV, V, and VI received gentamicin (100 mg/kg) intraperitoneally to induce kidney toxicity, with concomitant administration of normal saline (10 mL/kg), different doses of CAPE (100, 200, and 400 mg/kg), and ascorbic acid (200 mg/kg), respectively. Treatments were administered orally for 8 days. Twenty-four hours after the final dose, blood samples were collected, allowed to clot, and centrifuged to separate the serum for measuring urea, creatinine, and blood urea nitrogen (BUN). Furthermore, the levels of malondialdehyde (MDA) and glutathione (GSH) in kidney tissue were assessed.Results: The data indicated a decrease in tissue MDA, serum creatinine, urea, and BUN in the CAPE-treated groups. Moreover, the CAPE-treated groups exhibited elevated tissue CAT activity and higher GSH concentrations.Conclusion: The study concluded that CAPE displayed nephroprotective effects, which were possibly mediated via inhibition of oxidative stress.